(How) Does Initial Self-Control Undermine Later Self-Control in Daily Life?. (September 2018) - Wilkowski, Benjamin M.; Ferguson, Elizabeth Louise; Williamson, Laverl Z.; Lappi, Shaun K.
Past research suggests that self-control lapses occur more frequently following demanding experiences in daily life. However, the reason for these effects is debated. Three studies were therefore conducted to better understand self-control lapses. Exploratory analyses were conducted in Study 1 to identify possible effects. Studies 2 and 3 evaluated these effects' reliability. Two patterns were identified. First, initial desire–goal conflict predicted later increases in subjective fatigue. This was in turn related to less effective self-control attempts. Second, initial self-control attempts also led participants to enact desires more frequently. This latter effect occurred even when (and perhaps especially when ) those later desires were not resisted. In contrast, the strength model of self-control did not receive support, as initial self-control attempts did not affect the success of subsequent self-control attempts. These studies therefore suggest initial self-control does play an important role in producing later self-control lapses—just a different role than predicted by the strength model.